PEMBELAJARAN SENI BUDAYA BALI RELIGI HINDU DALAM SENI LUKIS ANAK-ANAK SEKOLAH DASAR SARASWATI TABANAN - Pendit, I Komang Dewanta (LP2M IKIP PGRI Bali, 2019)
The art of Hindu religious culture is a unification of the value of Hindu religious philosophy which is a union of Hinduism in Bali based on, the teachings of Hindu scriptures such as, Vedas, Purana, Itiasa even to the value of antiquity including about mithologi, tantri, animism , dynamism, polytheism, monotheism to the values ??of tradition, and modern become part of the idea of ??painting. It is a product of the cultivation of the human mind which is implemented through the works of painting including the painting of children.                The painting of children of Saraswati Tababanan Elementary School has a soul purity with a unique, simple naïf style, with irregular compositions, bright colors. The value of the art of culture that breathes Hindu religion as the basis of the idea of ??making the painting of elementary school children is the result of visualization learning from the sensory ability to the art culture product of religion which is seen absorbed from the environmental factors around them. This phase in religious view is called, Mitic-Literal Faith (Mithic-Literal Faith). This form of belief occurs aged 7-12 years. These logical operations begin to be concrete, and lead to a causal category. Children begin to distinguish between their own perspective and the perspective of others. This phase is also creatively the children begin to develop the imagination of his painting through techniques that have passed the phase of scribbling, the preschematic phase and the schematic phase, and begin to understand the more concrete form.